2018
DOI: 10.1155/2018/3709491
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Antiangiogenic Activity ofTurbinaria ornataAgardh andPadina australisHauck Ethanolic Extracts

Abstract: Brown macroalgae species are constantly reported as potential sources of bioactive compounds useful in inhibiting cell proliferation and vascular formation. Thus, this study was conducted to determine and compare the in vitro cytotoxic activities of Turbinaria ornata Agardh and Padina australis Hauck ethanolic extracts against baker's yeast (Saccharomyces cerevisiae) using the resazurin reduction test (RRT) and investigate their in vivo antiangiogenic activity through duck (Anas platyrhynchos) chorioallantoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Based on our results, GLE shows stronger cytotoxic activity compared to crude macroalgae extracts in other studies [53,80,81]. However, the cytotoxic activity of GLE was quite similar to Laurencia papillosa-125.8 ± 2.1 µg/mL and 121.…”
Section: Discussionsupporting
confidence: 57%
“…Based on our results, GLE shows stronger cytotoxic activity compared to crude macroalgae extracts in other studies [53,80,81]. However, the cytotoxic activity of GLE was quite similar to Laurencia papillosa-125.8 ± 2.1 µg/mL and 121.…”
Section: Discussionsupporting
confidence: 57%
“…Reportedly, T. ornata has potential therapeutic applications such as anticancer [27] anti-inflammatory [28] antiulcer [29] antibacterial [30] antidiabetic and antioxidant [31] antiangiogenic [32] and for cosmetics including oils, soaps, shower gels, shampoo, body oil, skin moisturizing creams and protective lotions in French Polynesia (www.pacifiquesud.com). The local people in Gulf of Mannar are already exploring the abundant resource of Sargassum species for industrial applications.…”
Section: Resultsmentioning
confidence: 99%
“…Padina australis, one of the brown seaweeds found in some Southeast Asian countries including Vietnam, Malaysia, Indonesia and Thailand, belongs to the class Heterokontophyta and a member of Phaeophyceae. Bioactive compounds that have been isolated from this species including polyphenols, flavonoids, alkaloids, saponins, steroids, terpenoids, tannins, fucoxanthin and fatty acids (Gunji et al, 2007;Haryani et al, 2010;Salosso et al, 2020;Shiney & Wilsy, 2014) that has been found to possess antiangiogenic, antibacterial, antituberculosis, antioxidant and antimicrobial activity (Canoy & Bitacura, 2018;Chiao-Wei et al, 2011;Latifah et al, 2019;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%